Pengaruh Percobaan Sains Sederhana Terhadap Motorik Halus Anak Usia 5-6 Tahun - Sri Rika Amriani.H; Fitrianti Abdullah (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
This study aims to determine the effect of simple science experiments on fine motor skills in children aged 5-6 years Ra Islam Nurul Quddus. The research approach used is a quantitative approach with a Quasi Experiment Design. The population in this study were children aged 5-6 years Islam Nurul Quddus. Sampling in this research is purposive sampling. The sample in this study were 12children with 6 children as the experimental group and 6 children as the control group. Data collection techniques used are descriptive statistical analysis and non-parametric analysis. Based on the results of the study, it can be concluded that the fine motor skills of children who were treated with finger painting activities in the experimental group were better than the control group. The results of data analysis obtained Asym (2-tailed) = 0.026 <0.05 H1 accepted and H0 is rejected, meaning that the fine motor skills in the experimental class are better than the control class, this proves that the simple science experiment method with finger painting has an effect on improving fine motor skills. child.